The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fonc.2022.849447
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Model for Classifying Metastatic Epidural Spinal Cord Compression on MRI

Abstract: BackgroundMetastatic epidural spinal cord compression (MESCC) is a devastating complication of advanced cancer. A deep learning (DL) model for automated MESCC classification on MRI could aid earlier diagnosis and referral.PurposeTo develop a DL model for automated classification of MESCC on MRI.Materials and MethodsPatients with known MESCC diagnosed on MRI between September 2007 and September 2017 were eligible. MRI studies with instrumentation, suboptimal image quality, and non-thoracic regions were excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Most recently, Hallinan et al (2022) developed a deep learning model for the prediction of low and high-grade Bilsky classification on MRI of the thoracic spine. On internal and external testing, the DL model showed high agreement (κ = 0.92-0.94, p < 0.001) for two-grade Bilsky classification, which was similar to specialist labelers (κ = 0.95-0.98, all p < 0.001), including a spine surgeon, a radiation oncologist, and a radiologist [36].…”
Section: Discussionmentioning
confidence: 55%
“…Most recently, Hallinan et al (2022) developed a deep learning model for the prediction of low and high-grade Bilsky classification on MRI of the thoracic spine. On internal and external testing, the DL model showed high agreement (κ = 0.92-0.94, p < 0.001) for two-grade Bilsky classification, which was similar to specialist labelers (κ = 0.95-0.98, all p < 0.001), including a spine surgeon, a radiation oncologist, and a radiologist [36].…”
Section: Discussionmentioning
confidence: 55%
“…Applications of deep learning models goes beyond tumour detection and differentiation, and they have the ability to automatically generate meaningful parameters from MRI and other modalities. Hallinan et al [ 94 ] developed a deep learning model for automated classification of metastatic epidural disease and/or spinal cord compression on MRI using the Bilsky classification. The model showed almost perfect agreement when compared to specialist readers on internal and external datasets with kappas of 0.92–0.98, p < 0.001 and 0.94–0.95, p < 0.001, respectively, for dichotomous Bilsky classification (low versus high grade).…”
Section: Discussionmentioning
confidence: 99%
“…MSCC is a debilitating complication in cancer patients with spinal metastasis, and its incidence is expected to rise due to improving cancer treatments and survival [6,166]. As it is a time-sensitive diagnosis, prompt radiological evaluation within 24 h is necessary to avoid permanent neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang DL tools in image interpretation have seen substantial growth over the past few years. In a recently published study by Hallinan et al (2022) [166], axial T2-weighted images of 177 MR spine studies in MSCC patients from Sept 2007 to Sept 2017 were utilized to create a DL model employing convolutional neural networks for automated MSCC classification into dichotomized Bilsky gradings (low-grade Bilsky was defined as Grade 0 to 1b, while high-grade Bilsky was defined as Grade 1c to 3). Internal testing on 38 MRI spine studies and external testing on 32 MRI spine studies showed near-perfect agreement of the DL model and other subspecialist readers (including a musculoskeletal radiologist, neuroradiologist, spine surgeon and radiation oncologist, all with at least 5 years of clinical experience) with the reference standard (internal testing kappas = 0.92-0.98, p < 0.001; external testing kappas = 0.94-0.95, p < 0.001).…”
Section: Deep Learning (Dl) In Mscc Imagingmentioning
confidence: 99%